2019
DOI: 10.2147/cmar.s192845
|View full text |Cite
|
Sign up to set email alerts
|

<p>High expression of dedicator of cytokinesis 1 adversely influences the prognosis of acute myeloid leukemia patients undergoing allogeneic hematopoietic stem cell transplantation</p>

Abstract: Background: Overexpression of dedicator of cytokinesis 1 ( DOCK 1) has been confirmed as an unfavorable prognostic marker in acute myeloid leukemia (AML). Purpose: This study is to explore the clinical implications of DOCK1 on AML patients underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT). Patients and methods: We analyzed 71 de novo AML patients treated with allo-HSCT and divided them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In the present study, we focused on the hub gene TRIM32 since both DOCK1 and GLI2 had been discussed as adverse prognostic markers of AML in previous articles ( 31 34 ). To the best of our knowledge, it is the first time to report and validate the role of TRIM32 in AML.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on the hub gene TRIM32 since both DOCK1 and GLI2 had been discussed as adverse prognostic markers of AML in previous articles ( 31 34 ). To the best of our knowledge, it is the first time to report and validate the role of TRIM32 in AML.…”
Section: Discussionmentioning
confidence: 99%
“…as a rac-specific GEF, DOCK1 regulates phagocytosis, myoblastic fusion, cell migration and circular dorsal fold formation (9,10). Abnormal expression and activity of DOCK1 is associated with the malignant characteristics of multiple tumors (11)(12)(13)(14). increasing evidence has indicated that docK1 regulates invasion and metastasis by acting on downstream receptor tyrosine kinases (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%